Answer:
![\frac{3x+4}{x^2-6x+5}=\frac{-7}{4(x-1)} +\frac{19}{4(x-5)}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%2B4%7D%7Bx%5E2-6x%2B5%7D%3D%5Cfrac%7B-7%7D%7B4%28x-1%29%7D%20%2B%5Cfrac%7B19%7D%7B4%28x-5%29%7D)
Step-by-step explanation:
The given rational expression is:
![\frac{3x+4}{x^{2}-6x+5} = \frac{3x+4}{(x-1)(x-5)}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%2B4%7D%7Bx%5E%7B2%7D-6x%2B5%7D%20%3D%20%5Cfrac%7B3x%2B4%7D%7B%28x-1%29%28x-5%29%7D)
We can use concept of Partial Fractions to solve this problem. Let,
![\frac{3x+4}{(x-1)(x-5)}=\frac{A}{x-1} +\frac{B}{x-5}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%2B4%7D%7B%28x-1%29%28x-5%29%7D%3D%5Cfrac%7BA%7D%7Bx-1%7D%20%2B%5Cfrac%7BB%7D%7Bx-5%7D)
Multiplying both sides by (x - 1)(x - 5), we get:
![3x+4=A(x-5)+B(x-1)](https://tex.z-dn.net/?f=3x%2B4%3DA%28x-5%29%2BB%28x-1%29)
Substituting x = 5, we get:
![3(5)+4=A(5-5)+B(5-1)\\\\ 15+4=0+4B\\\\ 19=4B\\\\ B=\frac{19}{4}](https://tex.z-dn.net/?f=3%285%29%2B4%3DA%285-5%29%2BB%285-1%29%5C%5C%5C%5C%2015%2B4%3D0%2B4B%5C%5C%5C%5C%2019%3D4B%5C%5C%5C%5C%20B%3D%5Cfrac%7B19%7D%7B4%7D)
Substituting x = 1, we get:
![3(1)+4=A(1-5)+B(1-1)\\\\ 7=-4A\\\\ A=-\frac{7}{4}](https://tex.z-dn.net/?f=3%281%29%2B4%3DA%281-5%29%2BB%281-1%29%5C%5C%5C%5C%207%3D-4A%5C%5C%5C%5C%20A%3D-%5Cfrac%7B7%7D%7B4%7D)
Substituting the value of A and B, back in the original equation, we get:
![\frac{3x+4}{x^2-6x+5}=\frac{-7}{4(x-1)} +\frac{19}{4(x-5)}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%2B4%7D%7Bx%5E2-6x%2B5%7D%3D%5Cfrac%7B-7%7D%7B4%28x-1%29%7D%20%2B%5Cfrac%7B19%7D%7B4%28x-5%29%7D)
Answer:
1/9
Step-by-step explanation:
p = 2/18
p = 1/9
Answer:
1.5 a^4
Step-by-step explanation:
taking only numbers 3*5=15
15/10 = 1.5
taking a powers
a ^ (5+3-4)= a^4
1.5 a^4
Para resolver este problema, debe aplicar el procedimiento que se muestra a continuación:
1of the first figure in the image attached, is:
a ^ 2 = b ^ 2 + c ^ 2
c =
c=√(6 cm)^2-(4.8 cm)^2
c=3.6 cm
2. The area of the base of the first figure is:
A=BxH/2
A=3.6x4.8/2
A=8.64 cm^2
3. Therefore, the volume of the cone is:
V=(8.64 cm^2)(9.2 cm)
V=79.5 cm^3
Therefore, the answer is: C. 79.5 cm^3
Answer:
C. 59
Step-by-step explanation:
Hello There!
Remember the angles in a triangle add up to equal 180
So if we want to find a missing angle we subtract the given angles ( in this case 65 and 56) from 180
So missing angle = 180 - 65 - 56
180 - 65 = 115
115 - 56 = 59
So we can conclude that the missing angle has a measure of 59 degrees